Thermal-shock alkali activation — a new method of the preparation of nanoporous carbon adsorbents - Kucherenko, V.O.; Tamarkina, Yu.V.; Popov, A. F. (Reports of the National Academy of Sciences of Ukraine, 2016)
A new method for the preparation of nanoporous adsorbents from brown coals impregnated by alkalis MON (M = Li, Na, K) which combines a heat shock (800 °C) and the following isothermal holding is proposed. Varying the hol ding time (0—60 min) and the weight MOH/coal ratio (0.2—1.0 g/g) allows one to purposefully change the characteristics of a porous structure. The pore-forming activity increases in the row LiOH < NaOH < KOH. The heat shock and the holding (5 min) provide the basic (∼2/3) development of nanopores and determine the ratio of different size pores. The best adsorbent is characterized by a specific surface area of 1700 m2/g, total pore volume of 1.00 cm3/g, micropore volume of 0.71 cm3/g, and subnanopore volume of 0.42 cm3/g. This work is focused on the preparation of highly porous carbon materials for supercapacitors.